Optimalisasi Manajemen Kampanye Airdrop Kripto pada Blockchain Layer 1 dan Layer 2 dalam Fase Pengembangan: Studi Kasus Implementasi AirdropHub - Afif Kisnandhya Putra; Muhammad Nabil Musyarof (LPPM Universitas An Nuur, 2025)
This study analyzes the optimalization strategies for managing crypto airdrop campaigns on Layer 1 blockchain projects (e.g., Ethereum, Solana) and Layer 2 projects (e.g., Polygon, Arbitrum) during the development phase, with a focus on the AirdropHub platform based on native PHP MVC. This study evaluates the effectiveness of AirdropHub in supporting the planning, execution, and monitoring of airdrop campaigns, particularly through its daily quest management and wallet participation tracking features. A descriptive-analytical approach was used with a case study on AirdropHub, involving observations of system functionality, analysis of participation data, and evaluation of technological architecture. The results show that AirdropHub is capable of efficiently managing airdrop campaigns with CRUD features and activity tracking, although challenges such as system scalability and blockchain integration remain. This research provides practical insights for blockchain developers and community managers in designing structured, secure airdrop campaigns that encourage community engagement.